2020
DOI: 10.1159/000505992
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Metabolic Syndrome and Multiple Myeloma

Abstract: Multiple myeloma (MM) is a haematological malignancy arising from monoclonal proliferation of plasma cells in the bone marrow, resulting in the presence of paraproteins or M-protein in serum. The involvement of paraproteins produced by malignant plasma cells in the development of hyperlipidaemia and low-HDL cholesterol has been described, as has an association with MM and obesity, hypertension, and type 2 diabetes mellitus, and insulin resistance, that is, features of the metabolic syndrome (MS). There is an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 97 publications
1
31
0
1
Order By: Relevance
“…Metabolic syndrome represents a cluster of clinical features including central obesity, insulin resistance and hyperglycemia, dyslipidemia and hypertension [ 89 ]. There is increasing evidence for higher prevalence of the syndrome or its individual components in patients with MM [ 100 ]. The question arising is whether this phenomenon is due to the advanced age of MM patients, due to the disease itself or due to antimyelomaincluding steroids, chemotherapy, and bone marrow transplantation [ 100 , 101 ].…”
Section: Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic syndrome represents a cluster of clinical features including central obesity, insulin resistance and hyperglycemia, dyslipidemia and hypertension [ 89 ]. There is increasing evidence for higher prevalence of the syndrome or its individual components in patients with MM [ 100 ]. The question arising is whether this phenomenon is due to the advanced age of MM patients, due to the disease itself or due to antimyelomaincluding steroids, chemotherapy, and bone marrow transplantation [ 100 , 101 ].…”
Section: Metabolic Syndromementioning
confidence: 99%
“…There is increasing evidence for higher prevalence of the syndrome or its individual components in patients with MM [ 100 ]. The question arising is whether this phenomenon is due to the advanced age of MM patients, due to the disease itself or due to antimyelomaincluding steroids, chemotherapy, and bone marrow transplantation [ 100 , 101 ]. Obesity has been identified by several studies as risk factor for MM development and increased mortality [ 102 , 103 , 104 , 105 , 106 ].…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Plasma cells are transformed into protoplasmic cells by B lymphocytes after antigen stimulation, and protoplasmic cells evolve into mature plasma cells through processes such as differentiation and reproduction [ 20 ]. M protein is an abnormal immunoglobulin produced by the monoclonal malignant proliferation of plasma cells or B lymphocytes [ 21 ]. Studies have confirmed that the proportion of plasma cells and the level of M protein in patients with multiple myeloma are significantly increased [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Однако адипоциты могут продуцировать и проти вовоспалительные факторы, например адипонектин, ингибирующий сигнальный путь NFκB, а также ак тивирующий апоптоз ММклеток через киназу AMPK. С прогрессией ММ ассоциирована гипоадипонекти немия, которую может обеспечивать секреция ММ клетками ФНОα [16,40,41].…”
Section: адипоцитыunclassified